Belangke bamboo (gigantochloa pruriens) laminated board modified with polystyrene, citric, and boric acid: resistance from termite and decay attacks - Hartono, Rudi; Sutiawan, Jajang; Kusumah, Sukma Surya; Tarmadi, Didi; Wikantyoso, Bramantyo; Himmi, Setiawan Khoirul; Yusuf, Sulaeman; Zulfiana, Deni; Muhammad Roseley, Adlin Sabrina; Abu, Falah (North Carolina State University, 2024)
Polystyrene, citric, and boric acid are capable of enhancing the quality of bamboo as a raw material for laminated board (LB). Although the characteristics of the modified LB has met the JAS 234 (2003) standard, the resistance against termite and decay attacks was still unknown. In this work, a 6-h immersion time was used to immerse bamboo lamina in polystyrene, citric, and boric acid. Laminated board comprising 3 layers of 30 cm × 15 cm × 1.5 cm (length × width × thickness) were constructed using 280 g/m2 isocyanate adhesive from bamboo lamina using double-spread adhesive method. This was followed by resistance testing against termite wood and decay caused by T. versicolor and F. palustris using the JIS K 1571 (2010) standard. Parameters calculated after testing for termite included weight loss and mortality, while weight loss was determined after evaluating the decay using JIS standard. The results showed that modification with polystyrene, citric, and boric acid slightly increased the resistance of LB from belangke bamboo against termite and decay attacks. In comparison, samples modified with polystyrene had lower weight loss than others, which showed high resistance to attacks. This showed that modification with polystyrene could be recommended to improve the quality of LB from belangke bamboo.